Analysis of Daycare Agreements in the Legal Perspective of Treaties According to the Civil Code - Kania Putri Abubakrin; AAA Ngurah Tini Rusmini Gorda (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2022)
Child care occurs when a person accepts a child from another person, on the condition that he will take care of it and receive wages for the work and return it to its original condition. at the time specified in the agreement. The recipient of the deposit has the obligation to take care of his own child. In essence, all agreements made must be in accordance with the legal requirements of the agreement according to Article 1320 of the Civil Code. in accordance with Article 1320. This research is aimed at the development of civil science, namely by knowing how the standard of agreement for daycare management is and knowing the agreement according to Article 1320 of the Civil Code on child care agreements. used in this study is normative, where this study analyzes an agreement that is still not in accordance with Article 1320 of the Civil Code. From this provision, parents and the community are more selective in reading and understanding the contents of the agreement, because the child is entrusted.